1999
DOI: 10.1046/j.1525-1438.1999.99033.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical tumor characterization by transvaginal color flow Doppler ultrasound

Abstract: The aim of the study was to investigate the blood flow characteristics of benign cervical lesions and invasive cervical tumors and to determine if invasive cervical tumors can be predicted by transvaginal sonography (TVS) and color flow Doppler (CFD). The study design incorporated an open prospective collection of data from patients attending the Women's Cancer Center, University of Minnesota and the Sydney Women's Cancer Center. Inclusion criteria included patients with known benign or malignant cervical path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…13 Nevertheless, if our data are confirmed by prospective studies, evaluation of the uterine artery could be particularly useful in the follow-up of patients with cervical cancer during chemotherapy and/or radiotherapy, particularly as it has recently been demonstrated that bevacizumab, an antiangiogenic antibody, increases specific disease-free and overall survival in the advanced stages of gynecological neoplasms 20,21 including cervical cancer. 22 Furthermore, a pioneering study hypothesized and assumed that tumor size is strictly correlated to prognosis, 5 and knowledge of Doppler flow characteristics could be useful in monitoring patients, and could offer speculative advantages in predicting patients who will respond better to treatment.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…13 Nevertheless, if our data are confirmed by prospective studies, evaluation of the uterine artery could be particularly useful in the follow-up of patients with cervical cancer during chemotherapy and/or radiotherapy, particularly as it has recently been demonstrated that bevacizumab, an antiangiogenic antibody, increases specific disease-free and overall survival in the advanced stages of gynecological neoplasms 20,21 including cervical cancer. 22 Furthermore, a pioneering study hypothesized and assumed that tumor size is strictly correlated to prognosis, 5 and knowledge of Doppler flow characteristics could be useful in monitoring patients, and could offer speculative advantages in predicting patients who will respond better to treatment.…”
Section: Discussionmentioning
confidence: 62%
“…However, only a few studies have been published to date, and their results were contradictory. [11][12][13][14][15][16][17][18] Our hypothesis was that the blood flow characteristics in the uterine arteries may be influenced by local expansion of the cervical cancer, increased by neoangiogenesis tumor-linked.…”
Section: Discussionmentioning
confidence: 99%
“…However, this was challenged by Carter and colleagues (14) . None of these authors correlated intratumoral blood flow with tumor features.…”
Section: Discussionmentioning
confidence: 99%
“…The role of color Doppler parameters in the discrimination of benign from malignant ovarian neoplasms4–6, and in the analysis of vascularization in endometrial cancer7–9, has been extensively studied. Few data have been published on cervical tumors10–13, although some studies have tried to define the correlation between Doppler parameters and the pathological characteristics of cervical cancer14–17.…”
Section: Introductionmentioning
confidence: 99%